Correlates of sedentary behaviour among adults with hazardous drinking habits in six low- and middle-income countries. (March 2018) - Vancampfort, Davy; Stubbs, Brendon; Hallgren, Mats; Lundin, Andreas; Firth, Joseph; Koyanagi, Ai
Abstract: Sedentary behaviour is associated with poor mental health, diabetes and cardiovascular disease, all of which are a concern among hazardous drinkers. Little is known about sedentary behaviour and it's correlates in hazardous drinkers, particularly in low- and middle-income countries. We investigated correlates of sedentary behaviour among community-dwelling adults aged ≥18 years with hazardous drinking patterns in six low- and middle-income countries. Cross-sectional data were analyzed from the World Health Organization's Study on Global Ageing and Adult Health. Hazardous drinking was defined as consuming >7 (females) or >14 (males) standard drinks per week. Associations between time spent sedentary and a range of correlates were examined using multivariable linear and logistic regression. The mean time spent sedentary in 2142 individuals with hazardous drinking patterns (mean age = 45.7 years; 13% female) was 216±135 min/day. Nine percent (95%CI=6.1–13.2%) were sedentary for ≥8 h per day. Living in an urban setting and unemployment were strong sociodemographic correlates of being sedentary for ≥8 h per day. From a health-related perspective, weak grip strength, stroke and disability were associated with increasing time spent sedentary. The current data provides important guidance for future interventions across low- and middle-income countries to assist hazardous drinkers to reduce sedentary behaviour. Highlights: Unemployment is a strong correlate for sedentary behaviour in hazardous drinkers. Those living in cities are more sedentary than those living in rural areas. Weak grip strength, stroke and disability are associated with being sedentary.